7 - Development is Resistance - Tandon, Yash (Africa Development, 2021)
The main the argument of this article is that, in our epoch, resistance against imperial domination is the first law of motion of development. How did I come to this conclusion? I came to it through a critical look at the existing theories of development, and through my active participation in over fifty years of Africa’s struggle to ‘develop’. The article looks at various aspects of the theory and practice of ‘development’, focusing mainly on the theory as expounded by economic theoreticians for the last three hundred years. The article also makes use of specific cases or case studies to sharpen its main argument and support the conclusion reached. The discussion is situated firmly in the context of the harsh reality of imperialism. The west suffers from an acute case of amnesia when it comes to recognising imperialism … and its role in destroying the cultural, economic and social roots of Africa’s (admittedly slow) evolution into self-sustaining and respected members of the international community. Today, Africa’s economy is shattered – devastated – by the so-called ‘free trade’ dogma. I can say with some degree of authority as a political-economic historian that there has never existed anything called ‘free trade’ – never.